Regulation and Non-Compliance : Magnitudes and Patterns for India's Factories Act - Chatterjee, Urmila; Kanbur, Ravi (World Bank, Washington, DC, 2014)
Non-compliance with regulations by enterprises is said to be rife in developing countries. Yet there is limited systematic evidence of the magnitude of non-compliance at the enterprise level. Making innovative use of two complementary data sources, non-compliance for India's Factories Act has been quantified without the question of illegality ever being raised directly with enterprises. It is found that more than twice as many firms are not complying as are complying. Further, the number of non-compliant firms is much larger than the number of firms adjusting out of the regulation. Thus non-compliance with the Factories is a key feature of the "missing middle" in India. The main trends and patterns of non-compliance are explored herein and key issues for further analytical and policy research are highlighted.